2018
DOI: 10.1039/c8nr00502h
|View full text |Cite
|
Sign up to set email alerts
|

Diamond nanothread based resonators: ultrahigh sensitivity and low dissipation

Abstract: The recently synthesized ultrathin diamond nanothreads (NTHs) exhibit a variety of intriguing properties and are probably the most successful of many encouraging applications to be designed as resonators due to their ultrahigh sensitivity and low dissipation. Herein, we report via molecular dynamics that diamond nanothreads possess not only ultrahigh mass sensitivity but also a very high quality factor. On the one hand, the studied diamond nanothreads demonstrate an extreme mass resolution of ∼0.58 yg (1 yg = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Thus, a straightforward way to maximize the energy storage capacity of nanothread bundle is to utilize the full tensile potential of each constituent nanothread filaments. It is noted that experimental studies have shown that the carbon nanothreads can be partially saturated 41 , which could increase their elastic limit 42 . This provides the possibility of using partially saturated nanothreads at the outermost layer of the bundle to enhance the mechanical performance of a twisted bundle.…”
Section: Optimum Mechanical Energy Storage In Nanothread Bundlementioning
confidence: 99%
“…Thus, a straightforward way to maximize the energy storage capacity of nanothread bundle is to utilize the full tensile potential of each constituent nanothread filaments. It is noted that experimental studies have shown that the carbon nanothreads can be partially saturated 41 , which could increase their elastic limit 42 . This provides the possibility of using partially saturated nanothreads at the outermost layer of the bundle to enhance the mechanical performance of a twisted bundle.…”
Section: Optimum Mechanical Energy Storage In Nanothread Bundlementioning
confidence: 99%
“…For example, they may uniquely combine extreme strength with flexibility and resilience, [13][14][15] have higher load transference to polymer matrices than carbon nanotubes due to more irregular surface topography, [16][17] and may support torsional deformations ~3 times those of sp 2 nanotubes for which flattening degrades mechanical performance. 17 Modeling also suggests certain nanothreads may behave as resonators with higher quality factors than carbon nanotubes, 18 could exhibit electronic properties tunable by tensile strain, 19 and may show superplastic behavior. 20 Their thermal conductivity is predicted to be tunable depending on axial structural order.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 11 and Figure 12 show the relationship between the resonance frequencies and the added masses of the DNTs with an isolated SW defect and continuous SW defects. The approximate curve equation for the figures can be expressed as Equation ( 18 ) [ 59 , 60 ], which is applied for the first time in the DNT vibration analysis in this study. where m denotes the attached mass, is the natural frequency, is the resonant frequency with the attached mass, and is the constant obtained by fitting the analysis results.…”
Section: Resultsmentioning
confidence: 99%
“…Figures 11 and 12 show the relationship between the resonance frequencies and the added masses of the DNTs with an isolated SW defect and continuous SW defects. The approximate curve equation for the figures can be expressed as Equation ( 18) [59,60], which is applied for the first time in the DNT vibration analysis in this study.…”
Section: Vibration Analysismentioning
confidence: 99%